THE IMPACT OF BRAND IMAGE ON CUSTOMER SATISFACTION : A STUDY OF MAXX COFFEE IN SURABAYA - Verina Wijaya (Fakultas Ekonomi Universitas 45 Surabaya, 2018)
Today, since products and services are so easily replicable, companies face a challenge to differentiate themselves to compete in the market. One of the most effective ways to create difference in the market is by creating a strong brand. A strong brand image is intangible asset for companies that are difficult to imitate. This study examines the relationship between brand image and customer satisfaction. A hundred customers were used as the research sample, and the data was extracted using online questionnaires distributed to Maxx Coffee customers within Surabaya area. The data was then be analyzed with Linear Regression and be processed using SPSS 20.0. The result indicated that brand image positively affect customer satisfaction at Maxx Coffee brands in Surabaya. However, the results imply that brand image has only little contribution to customer satisfaction.